Usability of Fantom Encore® scaffold in non‐complex bifurcations–Analysis in bench models. Issue 2 (10th February 2021) - G. Toth, Gabor; Ono, Masafumi; Buschmann, Eva; Wu, Xinlei; Edl, Dominik; Onuma, Yoshinobu; Serruys, Patrick WJC; Wijns, William
Abstract: Objective: Present bench study aimed to evaluate whether technical characteristics of Fantom Encore® bioresorbable scaffold (BRS) allow to perform proximal optimization/side branch dilation/proximal optimization (POT‐SB‐POT) technique, as an adequate solution for bifurcation percutaneous coronary intervention. Methods: Two Fantom Encore® BRS platforms ( small with 3.0 mm nominal diameter, n = 7; and large with 3.5 mm nominal diameter, n = 7) were evaluated in bench models, which were designed according to Finet‐law and fitted to nominal scaffold diameter in the distal main branch (MB) and fitted to indicated maximal expansion capacity in the proximal main branch (MB). Results were evaluated by (a) fluoroscopy, (b) optical coherence tomography (OCT) and (c) micro‐computed tomography (μCT). Results: All procedures were performed according to the protocol. Careful review of the fluoroscopic loops by an independent operator did not reveal any strut fracture or major deformation. By OCT the overall rate of perfectly apposed struts in the bifurcation area was 15 ± 6% after SB opening, that increased significantly but remained low with 22 ± 9% after final POT ( p = .001). Compared to SB ballooning alone, significant benefit of final POT was found in rate of perfect apposition in the proximal MB (15 ± 12% vs. 26 ± 15%, respectively; p = .017) and at the abostial side of polygon of confluence (7 ± 9% vs. 16 ± 13%, respectively; p = .005). μCT analysis revealed a single strut fracture in one case with the small platform, while four cases showed single or multiple strut fractures with the large platform. Conclusion: The mechanical characteristics of the device are not suitable for use of Conventional techniques for bifurcation PCI such as POT‐SB‐POT. The use of Fantom Encore® BRS for bifurcation PCI with relevant SB should not be encouraged.